Social Media as Platforms for Voter Mobilisation and Participation in Nigeria - Inobemhe, Kelvin (International Journal of Media and Communication Research, 2026)
In a functional democracy, participation in elections is considered as a duty of citizens. In modern times, social media platforms are powerful tools for communication and there is a growing adoption and utilisation. Ignoring these important platforms as tools for mobilisation could mean excluding a vibrant population who are users of the communication tools. Therefore, this study was conducted to examine the influence of social media as platforms for voter mobilisation and participation during the 2023 election in Nigeria and considered survey as research design also using online channels to administer the questionnaires. Select states of Edo, Delta and Rivers in the South-South region composed of the geographical scope of the study with 548 valid responses received from citizens and voters from the area. Findings demonstrated that social media were influential platforms for voter mobilisation and participation during the election. Findings further showed that various social media platforms such as Facebook, X and WhatsApp were prominently utilised as mobilisation tools and that their use influenced voting decision but not the general voter behaviour as widely found in many social media-related election mobilisation studies. The researchers concluded that though social media are of great influence on voters’ decisions but do not have absolute power on voter behaviour and recommended continuous and sustained use of platforms as mobilisation platforms. The socio-political implication of this study is the usefulness and effectiveness of social media platforms in political mobilisation and participation.